Hydrolysis of caprine and ovine milk proteins, brought about by aspartic peptidases from Silybum marianum flowers - Vairo Cavalli, Sandra Elizabeth (2008)
The flowers of cardoon (Asteraceae) are a rich source of aspartic peptidases which possess milk clotting activity – and are thus used in traditional cheesemaking in the Iberian Peninsula. This study was aimed at characterizing the enzymatic action of the aspartic peptidases present in flowers of Silybum marianum (L.) Gaertn. (Asteraceae), specifically upon degradation of caseins. The proteolytic activities toward Na-caseinates previously prepared from caprine and ovine milks were studied, in a comparative fashion, using urea-PAGE, tricine-SDS-PAGE, densitometry, electroblotting and sequencing. Caprine αs1- and β-caseins were degraded up to 68% and 40%, respectively, during 24 h of incubation. Only one important and well-defined band corresponding to a molecular weight of 14.4 kDa – i.e. a fragment of β-casein, was observed by 12 h of hydrolysis. By 24 h of incubation, ovine αs- and β-caseins were degraded up to 76% and 19%, respectively. In what concerns specificity, the major cleavage site in ovine caseinate was Leu99-Arg100 in αs1-casein.